Recuperação seletiva de ouro de pinos de placa de circuitos impressos empregando nanofibras funcionalizadas com Cyanex 272 - Bernardo, Heliano Clemente (2022)
Advances in technological development mean that the recovery of rare and strategic metals from secondary sources has become essential, due to the high demand for these metals in the production of electronic equipment. Contributing to this goal, the main purpose of this work was to develop Nylon 6 nanofibers modified with the Cyanex 272 organic extractant, for use in the selective recovery of gold present in printed circuit boards. The nanofibers were produced by the centrifugation technique, employing the Forcespinning® system and identified by scanning electron microscopy equipped with a secondary electron detector. The concentration of elements present in the PCI pins was determined by atomic absorption spectroscopy after leaching them with aqua regia. Gold concentrations in the extraction/stripping aqueous phases were performed by atomic absorption spectroscopy. The best extraction conditions for the separation and concentration of gold were 10% Cyanex 272, fixed pH of 1.5, contact time of 15 min, and solid:liquid ratio (S/L) of 1/700. Gold extraction efficiencies above 77% were achieved in this step. In the stripping step, efficiencies exceeding 85% were obtained using 1 M HCl, 1 M thiourea, S/L of 1/50, and contact time of 3 min. The nanofibers were evaluated in terms of their adsorption capacity, stability, and capacity for reuse in successive cycles. The results demonstrated the possibility of reuse of Nylon 6/Cyanex 272 nanofibers after at least five extraction and stripping cycles. These nanofibers provided high selectivity in the recovery of gold when applied using real leachate solutions, in the presence of other metals (lead, tin, zinc, and copper). The use of nanofibers modified with Cyanex 272 was shown to be an effective option for gold recovery, with lower environmental impacts, compared to conventional liquid-liquid extraction methods that require the use of organic solvents.